Alpha-synuclein overexpression induces epigenomic dysregulation of glutamate signaling and locomotor pathways. Issue 21 (14th May 2022) - Schaffner, Samantha L; Wassouf, Zinah; Lazaro, Diana F; Xylaki, Mary; Gladish, Nicole; Lin, David T S; MacIsaac, Julia; Ramadori, Katia; Hentrich, Thomas; Schulze-Hentrich, Julia M; Outeiro, Tiago F; Kobor, Michael S
Abstract: Parkinson's disease (PD) is a neurological disorder with complex interindividual etiology that is becoming increasingly prevalent worldwide. Elevated alpha-synuclein levels can increase risk of PD and may influence epigenetic regulation of PD pathways. Here, we report genome-wide DNA methylation and hydroxymethylation alterations associated with overexpression of two PD-linked alpha-synuclein variants (wild-type and A30P) in LUHMES cells differentiated to dopaminergic neurons. Alpha-synuclein altered DNA methylation at thousands of CpGs and DNA hydroxymethylation at hundreds of CpGs in both genotypes, primarily in locomotor behavior and glutamate signaling pathway genes. In some cases, epigenetic changes were associated with transcription. SMITE network analysis incorporating H3K4me1 ChIP-seq to score DNA methylation and hydroxymethylation changes across promoters, enhancers, and gene bodies confirmed epigenetic and transcriptional deregulation of glutamate signaling modules in both genotypes. Our results identify distinct and shared impacts of alpha-synuclein variants on the epigenome, and associate alpha-synuclein with the epigenetic etiology of PD.